Konstruksi Sosial Identitas “Muslim Ideal” dalam Perilaku Belajar Peserta Didik Analisis Relasi Kuasa dan Epistemologi Pendidikan Islam di SDIT Kayyatal Jihaaz - Supian Munawar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study critically explores psychological learning behavior within the social construction of the “ideal Muslim” identity among students at SDIT Kayyatal Jihaaz PPI 220 Margaluyu, Tanjungsari, Sumedang. Using a qualitative-critical approach with a case study design, this research examines the interaction between students’ psychological dynamics, daily learning practices, and the institutional environment that shapes religious identity formation. The theoretical framework integrates Berger and Luckmann’s sociology of knowledge, Skinner’s behaviorist psychology, Bandura’s social cognitive theory, Foucault and Bourdieu’s perspectives on power relations, and Islamic educational epistemology. Data were analyzed to reveal how school rules, teacher authority, symbolic discipline, and repeated religious routines influence students’ obedience, motivation, and self-perception within everyday school life. The findings indicate that psychological manifestations in children’s learning behavior are produced through externalization, objectivation, and internalization of value systems mediated by the symbolic power of teachers. Formal compliance at the surface level often conceals passive psychological resistance caused by rigid regulatory dominance. This study formulates the Reflective Islamic Identity Construction model as a strategic framework to transform formalistic piety into a more authentic, reflective, and internalized Muslim identity.